Atomistic modelling of friction of Cu and Au nanoparticles adsorbed on graphene - Khomenko, A.V.; Prodanov, N.V.; Persson, B.N.J. (Condensed Matter Physics, 2013)
We present classical molecular dynamics calculations of the behavior of copper and gold nanoparticles on a graphene sheet, sheared with a constant applied force Fa. The force Fs acting on the particle from the substrate depends on the material of the nanoparticles (Au or Cu), and exhibits a sawtooth dependency on time, which we attribute to local commensurability between the metal nanoparticle surface atomic positions with the graphene lattice. The time-averaged value of Fs (the friction force) acting on Au nanoparticles increases linearly with the contact area, having slopes close to the experimentally observable ones. A qualitative model is proposed to explain the observed results. Представлено розрахунки на основi класичної молекулярної динамiки поведiнки мiдних i золотих наночастинок на шарi графену, що зсуваються з постiйною прикладеною силою Fa. Сила Fs, що дiє на частинку з боку пiдкладки, залежить вiд матерiалу наночастинок (Au або Cu) i демонструє пилкоподiбну залежнiсть вiд часу, яка обумовлена локальною сумiрнiстю мiж положеннями атомiв поверхнi металевих наночастинок та ґратки графену. Середнє за часом значення Fs (сила тертя), що дiє на Au наночастинки, збiльшується лiнiйно з площею контакту з нахилами близькими до експериментально спостережуваних. Запропоновано якiсну модель для пояснення результатiв, що спостерiгаються.